Perancangan Desain Feed Instagram Untuk Produk Colar Living (International Forum of Researchers and Lecturers, 2024)
The evolution of social media has transformed it into an effective promotional platform for companies to convey product information. This research aims to analyze the design of Instagram content, focusing on Colar Living products. The methodology involves discussions, interviews, and observations to comprehend the design concept. Research findings reveal four key aspects influencing the visual appeal of Instagram content: color selection, typography, product photography, and layout composition. The importance of color consistency with the brand image, clear typography, high-quality lifestyle product photography, and layout arrangement following design principles. With the right design strategy, Instagram content can enhance brand awareness and influence audience purchasing decisions. Recommendations are provided to optimize Instagram as a tool for digital promotion, particularly through the Instagram feed in the era of the creative industry.